Crystallisation of magmatic topaz and implications for Nb-Ta-W mineralisation in F-rich silicic melts - The Ary-Bulak ongonite massif - Agangi, Andrea; Kamenetsky, V.; Hofmann, A.; Przybylowicz, W.; Vladykin, N. (Elsevier, 2014)
Textural, mineralogical and geochemical data on F-rich rhyolite (ongonite) from the Ary-Bulak massif of eastern Transbaikalia help constrain the formation of magmatic topaz. In these rocks, topaz occurs as phenocrysts, thus providing compelling evidence for crystallisation at the orthomagmatic stage. Cathodoluminescence images of topaz and quartz reveal growth textures with multiple truncation events in single grains, indicative of a dynamic system that shifted from saturated to undersaturated conditions with respect to topaz and quartz. Electron microprobe and Raman analyses of topaz indicate near-pure F composition [Al2SiO4F2], with very limited OH replacement. Laser ablation ICP-MS traverses revealed the presence of a large number of trace elements present at sub-ppm to hundreds of ppm levels. The chemical zoning of topaz records trace element fluctuations in the coexisting melt. Concentrations of some trace elements (Li, Ga, Nb, Ta and W) are correlated with cathodoluminescence intensity, thus suggesting that some of these elements act as CL activators in topaz.The study of melt inclusions indicates that melts with different F contents were trapped at different stages during formation of quartz and topaz phenocrysts, respectively. Electron microprobe analyses of glass in subhedral quartz-hosted melt inclusions indicate F ≤ 1.2 wt.%, whereas irregular-shaped melt inclusions hosted in both topaz and quartz have F ≤ 9 wt.%. Cryolithionite [Na3Li3Al2F12] coexists with glass in irregular inclusions, implying high Li contents in the melt. The very high F contents would have increased the solubility of Nb, Ta and W in the melt, thus allowing progressive concentration of these elements during magma evolution. Crystallisation of Nb–Ta–W-oxides (W-ixiolite and tantalite–columbite) may have been triggered by separation of cryolithionite, which would have caused F and Li depletion and consequent drop in the solubility of these elements.